Investment in Road Infrastructure and Its Impact on the Economic Development: An Analysis Approach to the Infrastructure Case in Colombia (1993-2014) (2018)
The objective of this article is to analyze the evolution and the relationship between investment and road infrastructure and the economic development of Colombia, making a comparison with some Latin American countries. Furthermore, the relationship through macroeconomic indicators and road infrastructure is established, including Colombia’s competitiveness compared to neighbor countries. In order to achieve this, the historical records are analyzed through different generations of concessions which have been created between 1993 and 2014; the article is further intended to review the bibliography associated to the international tendency to involve more participation of private sector in the development of road infrastructure projects through public and private associations as the specific involvement mechanisms.